Elements of voice first style : a practical guide to voice user interface design. - Bouzid, Ahmed; Ma, Weiye (O'Reilly Media, 2022)
If you're a new or experienced designer of conversational voice first experiences, this handy reference provides actionable answers to key aspects of eyes-busy, hands-busy, voice-only user interfaces. Designed as a companion to books about conversational voice design, this guide includes important details regarding eyes-free, hands-free, voice-only interfaces delivered by Amazon Echo, Google Nest, and a variety of in-car experiences. Authors Ahmed Bouzid and Weiye Ma provide far-field voice best practices and recommendations in a manner similar to The Elements of Style, the popular American English writing style guide. Like that book, The Elements of Voice First Style provides direct, succinct explanations that focus on the essence of each topic. You'll find answers quickly without having to spend time searching through other sources. With this guide, you'll be able to: Craft just the right language to enable your voicebot to effectively communicate with humans Create conversational voice interfaces that are robust enough to handle errors and failures Design highly usable conversational voice interfaces by paying attention to small details that can make or break the experience Build a design for a voice-only smart speaker that doesn't require customers to use their eyes or hands.